Fostering Economic Resilience in Pangkalpinang: A Qualitative Investigation into MSME Development Strategies - Dian Prihardini Wibawa; Khairiyansyah Khairiyansyah; Nurwasya Nurwasya; Ria Atlantica (Equity: Jurnal Ekonomi, 2023)
Micro, small and medium enterprises (MSMEs) have a significant role in the economies of developing countries. After the Covid-19 pandemic, the transformation of MSMEs needs to be strengthened through optimizing the use of digital technology. MSME development is carried out through the pillars of corporatization, capacity building, and financing policies, in order to create productive, innovative, and adaptive MSMEs. The number of cooperatives and MSMEs in Pangkalpinang City in 2022 will reach 23,119 MSMEs and is the largest sector in absorbing labor in Pangkalpinang City. Optimizing the role of MSMEs as the backbone of the economy will continue to be directed at efforts to increase productivity and inclusive regional economic growth, through adaptation to digital changes. This study is a strategic step in developing cooperatives and SMEs to increase regional economic growth to provide answers to current problems. The data used in this study are qualitative data and quantitative data. Data collection techniques are questionnaires, interviews and documentation. This study uses fishbone diagram analysis and SWOT analysis. The results of this study are that MSMEs in Pangkalpinang City are in quadrant I position. This means that MSMEs are advised to carry out an aggressive strategy by using internal strengths to take advantage of external opportunities to achieve increased MSME growth. Weak elements of the marketing strategy for Cooperatives and MSMEs in Pangkalpinang City are caused by weak digital marketing factors, product innovation, and partnerships with market places, startups, and others